Deciphering the roles of unknown/uncharacterized genes in plant development and stress responses - Wang, Xi; Wang, Baoshan; Yuan, Fang (Frontiers in Plant Science, 2023)
In recent years, numerous genes that encode proteins with specific domains that participate in different biological processes or have different molecular functions have been identified. A class of genes with typical domains whose function has rarely been identified and another type of genes with no typical domains have attracted increasing attentions. As many of these so-called as unknown/uncharacterized (U/U) genes are involved in important processes, such as plant growth and plant stress resistance, there is much interest in deciphering their molecular roles. Here, we summarize our current understanding of these genes, including their structures, classifications, and roles in plant growth and stress resistance, summarize progress in the methods used to decipher the roles of these genes, and provide new research perspectives. Unveiling the molecular functions of unknown/uncharacterized genes may suggest strategies to fine-tune important physiological processes in plants, which will enrich the functional network system of plants and provide more possibilities for adaptive improvement of plants.